The influence of using platelet rich plasma for post-extraction wound healing process - Oscar, Franky; Mangundjaja, Sunardhi; Yusuf, Makmuri; Pontjo, Bambang (Padjadjaran Journal of Dentistry, 2010)
Wound healing process characterized by specific processes of inflammation, proliferation, and maturation. It was coordinated by the regenerating and healing factors, including growth factor. Platelet-rich plasma was a blood component that separated from blood cell plasma, which contains a lot of growth factors for increased wound healing. The objective of this research was to observe the effect of the application of platelet-rich plasma for wound healing. The true experimental factorial design research was done to 24 rabbits (Oryctolagus cuniculus) which have been performed tooth extraction and application of platelet-rich plasma. These rabbits were terminated on 3rd, 7th, and 14th day, and the lower jaw region where the tooth had been extracted were cropped stained with hematoxylin-eosin for fibroblast and collagen histopathology examination. Based on ANOVA statistical analysis, the mean of fibroblast on the experimental group was 52.00+19.18 higher than the control group 24.83+10.46. Statistical tests showed a significant result of platelet-rich plasma application to fibroblast amount (p < 0.001). Collagen mean on the experimental group was 30.25+9.33 higher than the control group 13.75+6.96. It was significant statistically (p = 0.001). The conclusion of this research that wound healing process was influenced by the application of platelet-rich plasma.